Effectiveness of contingent screening for placenta accreta spectrum disorders based on persistent low‐lying placenta and previous uterine surgery. (2nd January 2021) - Coutinho, C. M.; Giorgione, V.; Noel, L.; Liu, B.; Chandraharan, E.; Pryce, J.; Frick, A. P.; Thilaganathan, B.; Bhide, A.
ABSTRACT: Objectives: Maternal mortality related to placenta accreta spectrum (PAS) disorders remains substantial when diagnosed unexpectedly at delivery. The aim of this study was to evaluate the effectiveness of a routine contingent ultrasound screening program for PAS. Methods: This was a retrospective study of data obtained between 2009 and 2019, involving two groups: a screening cohort of unselected women attending for routine mid‐trimester ultrasound assessment and a diagnostic cohort consisting of women referred to the PAS diagnostic service with a suspected diagnosis of PAS. In the screening cohort, women with a low‐lying placenta at the mid‐trimester assessment were followed up in the third trimester, and those with a persistent low‐lying placenta (i.e. placenta previa) and previous uterine surgery were referred to the PAS diagnostic service. Ultrasound assessment by the PAS diagnostic service consisted of two‐dimensional grayscale and color Doppler ultrasonography, and women with a diagnosis of PAS were usually managed with conservative myometrial resection. The final diagnosis of PAS was based on a combination of intraoperative clinical findings and histopathological examination of the surgical specimen. Results: In total, 57 179 women underwent routine mid‐trimester fetal anatomy assessment, of whom 220 (0.4%) had a third‐trimester diagnosis of placenta previa. Seventy‐five of these women were referred to the PAS diagnostic service because of a history of uterine surgery, and 21 of 22 cases of PAS were diagnosed correctly (sensitivity, 95.45% (95% CI, 77.16–99.88%) and specificity, 100% (95% CI, 99.07–100%)). Univariate analysis demonstrated that parity ≥ 2 (odds ratio (OR), 35.50 (95% CI, 6.90–649.00)), two or more previous Cesarean sections (OR, 94.20 (95% CI, 22.00–656.00)) and placenta previa (OR, 20.50 (95% CI, 4.22–369.00)) were the strongest risk factors for PAS. In the diagnostic cohort, there were 173 referrals, with one false‐positive and three false‐negative diagnoses, resulting in a sensitivity of 96.63% (95% CI, 90.46–99.30%) and a specificity of 98.81% (95% CI, 93.54–99.97%). Conclusions: A contingent screening strategy for PAS is both feasible and effective in a routine healthcare setting. When linked to a PAS diagnostic and surgical management service, adoption of such a screening strategy has the potential to reduce the maternal morbidity and mortality associated with this condition. However, larger prospective studies are necessary before implementing this screening strategy into routine clinical practice. © 2020 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of International Society of Ultrasound in Obstetrics and Gynecology. Abstract : This article's abstract has been translated into Spanish and Chinese. Follow the links from the abstract to view the translations. RESUMEN: Eficacia de la detección contingente para los trastornos del espectro de la placenta acreta a partir de la placenta baja persistente y en la cirugía uterina previa Objetivos: La mortalidad materna relacionada con los trastornos de la gama espectral de la placenta acreta (EPA) sigue siendo considerable cuando se diagnostica de forma inesperada en el momento del parto. El objetivo de este estudio fue evaluar la efectividad de un programa rutinario de detección contingente mediante ecografía para el EPA. Métodos: Este fue un estudio retrospectivo de datos obtenidos entre 2009 y 2019, en el que participaron dos grupos: una cohorte de detección de mujeres no seleccionadas que acudieron a la evaluación ecográfica rutinaria de mitad de trimestre y una cohorte de diagnóstico, integrada por mujeres remitidas al servicio de diagnóstico del EPA con un presunto diagnóstico del EPA. En la cohorte de detección, a las mujeres con una placenta baja en la evaluación de mitad de trimestre se les hizo un seguimiento en el tercer trimestre, y a aquellas con una placenta baja persistente (es decir, placenta previa) que habían tenido cirugía uterina previa se las remitió al servicio de diagnóstico del EPA. La evaluación ecográfica por el servicio de diagnóstico del EPA consistió en una ecografía Doppler bidimensional en escala de grises y en color, y a las mujeres con diagnóstico del EPA se las trató habitualmente con una resección conservadora del miometrio. El diagnóstico final del EPA se basó en una combinación de indicadores clínicos intraoperatorios y el examen histopatológico de la muestra quirúrgica. Resultados: En total, 57179 mujeres se sometieron a una evaluación rutinaria de la anatomía fetal a mitad del trimestre, de las cuales a 220 (0, 4%) se les diagnosticó con placenta previa en el tercer trimestre. Setenta y cinco de estas mujeres fueron remitidas al servicio de diagnóstico del EPA, debido a su historial de cirugía uterina, y 21 de los 22 casos de EPA fueron diagnosticados correctamente (sensibilidad, 95, 45% (IC 95%, 77, 16–99, 88%) y especificidad, 100% (IC 95%, 99, 07–100%)). El análisis univariante demostró que la paridad ≥2 (razón de momios (RM), 35, 50 (IC 95%, 6, 90–649, 00)), dos o más cesáreas previas (RM, 94, 20 (IC 95%, 22, 00–656, 00)) y la placenta previa (RM, 20, 50 (IC 95%, 4, 22–369, 00)) fueron los factores de riesgo más fuertes para el EPA. En la cohorte de diagnóstico, se remitió a 173 mujeres, entre las cuáles hubo un diagnóstico de falso‐positivo y tres diagnósticos de falsos‐negativos, lo que dio como resultado una sensibilidad del 96, 63% (IC 95%, 90, 46–99, 30%) y una especificidad del 98, 81% (IC 95%, 93, 54–99, 97%). Conclusiones: La adopción de una estrategia de detección contingente para el EPA es tanto factible como eficaz en un entorno de atención sanitaria rutinaria. Cuando se asocia a un servicio de diagnóstico y gestión quirúrgica del EPA, la adopción de esa estrategia de detección podría reducir la morbilidad y la mortalidad maternas asociadas a esta afección. Sin embargo, se necesitan estudios prospectivos más amplios antes de aplicar esta estrategia de detección en la práctica clínica habitual. © 2020 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of International Society of Ultrasound in Obstetrics and Gynecology. 摘要: 基于持续性低置胎盘和以前的子宫手术对胎盘植入性疾病(PAS)进行酌情筛查的有效性 目的: 在分娩时出乎意料地诊断为胎盘植入性疾病(PAS)时，与之相关的产妇死亡率仍然较高。本研究旨在为PAS评估一项常规超声酌情筛查计划的有效性。 方法: 这是对2009年至2019年之间所获数据进行的一项回顾性研究，涉及两组:一组为筛检队列，由未经选择的参加常规孕中期超声评估的孕妇组成；另一组为诊断队列，由因疑似PAS诊断而被转介至PAS诊断服务的孕妇组成。在筛检队列中，孕中期评估时有低置胎盘的妇女得到了晚期妊娠随访，而那些有持续性低置胎盘(如前置胎盘)和以前经历过子宫手术的妇女则被转介至PAS诊断服务。由PAS诊断服务进行的超声评估包括二维灰度图和彩色多普勒超声，被诊断为PAS的妇女则通常采取保守的子宫肌层切除术来管理。PAS的最终诊断是根据术中临床发现和对手术标本进行组织病理学检查的结合而得出的。 结果: 总计57179名妇女进行了常规孕中期胎儿解剖评价，其中220名(0.4%)在晚期妊娠诊断为前置胎盘。在这些妇女中，有75名因有子宫手术史而被转介到PAS诊断服务；在22个病例中有21例得到正确诊断(敏感度，95.45%(95% CI，77.16—99.88%)；特异性，100%(95% CI，99.07—100%))。经单因素分析表明，胎次≥2(比值比(OR)，35.50 (95% CI，6.90—649.00))、以前进行过二次或二次以上的剖腹产手术(OR，94.20(95% CI，22.00—656.00))和前置胎盘(OR，20.50(95% CI，4.22—369.00))都是PAS的最强风险因素。在诊断队列中，有173个转介，包括一个假阳性和三个假阴性诊断，得到96.63%的敏感度(95% CI，90.46—99.30%)和98.81%的特异性((95% CI，93.54—99.97%)。 结论: 对PAS的酌情筛查策略在常规医疗保健环境中既可行又有效。当关联到PAS诊断和手术管理服务时，采取此种筛检策略有减少产妇死亡率和与PAS相关发病率的可能性。然而，在将这一筛检策略实施到常规临床实践中之前，有必要进行更大规模的前瞻性研究。© 2020 作者。威利父子公司(John Wiley & Sons Ltd)代表国际妇产科超声学会(ISUOG)出版《国际妇产超声杂志》(Ultrasound in Obstetrics & Gynecology)。